Immunogenicity against the Omicron Variant after mRNA-Based COVID-19 Booster Vaccination in Medical Students Who Received Two Primary Doses of the mRNA-1273 Vaccine - Hyemin Chung; Jongsung Lee; Kyungrok Minn; Jiyoung Lee; Soyoung Yun; Joung Ha Park; Min-Chul Kim; Seong-Ho Choi; Jin-Won Chung (Vaccines, 2022)
We evaluated the immune response against the Omicron variant after mRNA-based COVID-19 booster vaccination in medical students. We prospectively enrolled medical students who received two primary doses of the mRNA-1273 vaccine. The neutralizing response and the SARS-CoV-2-specific T-cell response was evaluated. A total of 56 serum samples were obtained before booster vaccination. Nineteen students (33.9%) developed COVID-19 two months after booster vaccination. Of 56 students, 35 students (12 infected and 23 uninfected) were available for blood sampling four months after booster vaccination. In comparison with uninfected students, infected students showed a significantly higher level of SARS-CoV-2-specific IgG (5.23 AU/mL vs. 5.12 AU/mL, p < 0.001) and rate of neutralizing response (96.22% vs. 27.18%, p < 0.001) four months after booster vaccination. There was no significant difference in the SARS-CoV-2-specific T-cell response. Among 23 infection-naive students, the neutralizing response was significantly higher in those who received the mRNA-1273 booster than in those who received the BNT162b2 booster (69.07% vs. 26.43%, p = 0.02). In our study, booster vaccination with mRNA-1273 instead of BNT162b2 was significantly associated with a higher neutralizing response.